(3GdeHOC hGdeYGO (B( (3YfO GdeTGFjf (B)s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO aEfi CQjO Gf Chd ai gPg GdebGdI Ydi MbjbI YfO GdeTGFjf GdeMUdjf s
(3BNQgG (B:s
(3hdcf eDKQ GdGjVGM hGdGNJUGQ hJbQjH GdHYjOGf hfSFd Gddg JYGdi Gf jLfHfG GdRjZ hGdRdd hGdGSJHOGO HGdQCi GdHGWd hEYJbGO GdYLH ajeG JQi hjaYd Je cJGH GdeHOC hGdeYGO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs